Getok Tular Learning Model: An Example from Bantul District Yogyakarta (Komunitas, 2022)
Learning in villages or remote areas is difficult for many reasons. However communities with the same perception with the existing creativity then it could be done by adopting learning with their own culture and habits. This study aimed to dissect and understand the phenomenon of gathuk tular learning model in water hyacinth woven learning of Bantul district, therefore it could be applied or used in other communities with similar characteristics. The problem was how to apply this learning model without knowing the characteristics? This study was phenomenology research with interview and observation as the research instruments. It was also analyzed in empirical and literature review. Research found that the getok tular learning model can be  applied in a community with high social interaction. To conduct a getok tular learning model, a lesson must be made as  simple as possible and must be done in practice or learning in doing, thus it is easy to imitate and transmit. Getokk tular learning model also can be used in community practice development.Keyword : Gathuk Tular learning model, community learning, sosial capital